Dual effect of curcumin on viability and motility of bovine sperm exposed to oxidative stress - Jeong Seok Hwa; Eun-Jin Kim; Ji Hyeon Ryu; Adrian S. Siregar; Chang Yoon Park; Changyong Choe; Dawon Kang (Journal of Animal Reproduction and Biotechnology, 2016)
Although cryopreservation of sperm is routinely used for clinical requirement, it has some problems, such as high generation of reactive oxygen species (ROS) and cold-shock. To reduce the detrimental damage in sperm, anti-oxidants were added to cryoprotectant for sperm. Curcumin is one of anti-oxidants, which are added in cryoprotectants. However, recent studies have demonstrated that curcumin decreases sperm viability and motility. This study was performed to identify the effect of curcumin on hydrogen peroxide (H2O2)-exposed bovine sperm, which were cryopreserved-thawed. In H2O2-exposed bovine sperm, reactive oxygen species (ROS) were significantly reduced by treatment with curcumin in a dose-dependent manner (p < 0.05). Among tested concentrations of curcumin (1 to 50 μM), 30 and 50 μM curcumin showed anti-oxidant effect on H2O2-induced ROS generation. On the other hand, combination of 30 or 50 μM curcumin with anti-oxidant H2O2 increased the percentage of apoptotic sperm compared to only H2O2 treatment. Sperm viability was also decreased in the combination of 30 or 50 μM curcumin with H2O2 as judged by FDA/PI staining. H2O2?induced decrease in sperm progressive motility was recovered by treatment with 1 μM curcumin. These results show that high concentration of curcumin has anti-oxidant effect, but it has also cytotoxic effect on bovine sperm. Sperm viability and motility might be more affected by cytotoxic signals of curcumin compared to antioxidant signals.